As práticas de si no ensino médio: por um ensino de filosofia para o cuidado de si - Sousa, Antônio Alex Pereira de (2019)
This research analyzed the conditions and possibilities of the displacement of the concept of self-practices, analyzed by Michel Foucault (1926-1984) in his latest research, to think about the teaching of Philosophy in Brazilian secondary education. The self-practices were exercises used by the masters of care to carry out the test of truth, a process in which the subject reflects and freely transforms it into a principle of thought and action. The master of care was the one who, in Greco-Roman antiquity, by knowing how to take care of himself, knew how to take care of others, leading them to have dominion over themselves. Most of the masters analyzed by Foucault are philosophers, which is why they were thought to be examples of life and teaching practices that can help in reflection and incitement to new ways of teaching Philosophy today. The objective of care was to constitute a life supported by moral and ethical values, as a unique, singular and beautiful work of art. For the development of the research, a bibliographic review of the latest courses, interviews and books published by Michel Foucault was carried out in order to understand the concepts of self-care and self-knowledge, as well as their relations with ethics and politics. The concepts of self-practices and master of care were also analyzed. In order to understand the reality of teachers and the distances and approximations between these teachers and the masters of antiquity care, interviews were carried out with five Philosophy teachers from public schools who teach classes in Fortaleza. The analysis of the collected data took place in an analytical way, looking for examples of practices of the self in the present. The motivation of the present research was the absence of practical examples that could prove what the textbooks on the teaching of Philosophy presented theoretically. The feeling of absence of these practices was stimulated by the reading of what became known as the ethical moment of Foucault's philosophical production. From the results obtained, there is an example of several practices carried out in high schools that can enable students to prove the truth, approaching what Foucault called self-care and care for the other. Other implications arising from the research were suggestions for the degree courses in Philosophy, the education departments, schools and teachers to stimulate the creation and development of pedagogical practices in the teaching of Philosophy that stimulate the formation of ethical subjects who care for themselves and take care of others.